2020
DOI: 10.1264/jsme2.me20078
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Tomato Bacterial Wilt by Foliar Spray Application of a Novel Strain of Endophytic <i>Bacillus</i> sp.

Abstract: The aim of the present study was to identify a strain of endophytic Bacillus species that control tomato bacterial wilt by foliar spray application. Fifty heat-tolerant endophytic bacteria were isolated from the surface-sterilized foliar tissues of symptomless tomato plants that had been pre-inoculated with the pathogen Ralstonia pseudosolanacearum. In the primary screening, we assessed the suppressive effects of a shoot-dipping treatment with bacterial strains against bacterial wilt on tomato seedlings grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…In the recent years, Bacillus spp. has been widely studied as a potential biological control agent [25] . Bacillus can produce various types of diffusible substances and VOCs with strong inhibitory activity against pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, Bacillus spp. has been widely studied as a potential biological control agent [25] . Bacillus can produce various types of diffusible substances and VOCs with strong inhibitory activity against pathogenic fungi.…”
Section: Discussionmentioning
confidence: 99%
“…The low infection of B. cinerea in treated grapevine plants may be due to the high amount of P. protegens MP12 detected on the leaves in microbiological analysis conducted after foliar spraying. Fu et al [ 51 ] found about 2.5 log(CFU g −1 ) of Bacillus sp. strains after 14 days after foliar spraying, a very low concentration when compared with the data reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Full-length 16S rRNA gene sequences were elucidated as suggested by Fu et al (2020) for a more precise taxonomic classification. The 16S rRNA gene sequences of the strains were submitted to the GenBank database.…”
Section: Methodsmentioning
confidence: 99%